Some aspects of the research in the Laboratory of the Musée de la Musique, Paris Cité de la musique - Vaiedelich, Stephane (Archeomatica, 2019)
Experience The Musée de la Musique has a research and restoration laboratory that combines applied research dedicated to the study and conservation of musical instruments while also providing services linked to the collection. The activity of the laboratory falls within the scope of the study of the material and cultural object represented by the musical instrument and the values its legacy is leaving. The research conducted there has a concrete application in the conception and implementation of the conservation choices regarding the Musée's collection: pre-emptive or curative conservation, presentation of works of art as part of different exhibitions, and obviously the maintenance of their working order.